Thyroid cancer susceptibility polymorphisms: confirmation of loci on chromosomes 9q22 and 14q13, validation of a recessive 8q24 locus and failure to replicate a locus on 5q24. Issue 3 (25th January 2012) - Jones, Angela M; Howarth, Kimberley M; Martin, Lynn; Gorman, Maggie; Mihai, Radu; Moss, Laura; Auton, Adam; Lemon, Catherine; Mehanna, Hisham; Mohan, Hosahalli; Clarke, Susan E M; Wadsley, Jonathan; et al.
Abstract : Five single nucleotide polymorphisms (SNPs) associated with thyroid cancer (TC) risk have been reported: rs2910164 (5q24); rs6983267 (8q24); rs965513 and rs1867277 (9q22); and rs944289 (14q13). Most of these associations have not been replicated in independent populations and the combined effects of the SNPs on risk have not been examined. This study genotyped the five TC SNPs in 781 patients recruited through the TCUKIN study. Genotype data from 6122 controls were obtained from the CORGI and Wellcome Trust Case-Control Consortium studies. Significant associations were detected between TC and rs965513A (p=6.35×10 −34 ), rs1867277A (p=5.90×10 −24 ), rs944289T (p=6.95×10 −7 ), and rs6983267G (p=0.016). rs6983267 was most strongly associated under a recessive model (PGG vs GT + TT =0.004), in contrast to the association of this SNP with other cancer types. However, no evidence was found of an association between rs2910164 and disease under any risk model (p>0.7). The rs1867277 association remained significant (p=0.008) after accounting for genotypes at the nearby rs965513 (p=2.3×10 −13 ) and these SNPs did not tag a single high risk haplotype. The four validated TC SNPs accounted for a relatively large proportion (∼11%) of the sibling relative risk of TC, principally owing to the large effect size of rs965513 (OR 1.74).